Assessment of the potential allelopathic effects of Pennisetum purpureum Schumach. on the Germination and Growth of Eleusine indica (L.) Gaertn. - Ismail, B.S.; Tan, P.W.; Chuah, T.S. (Universiti Kebangsaan Malaysia, 2015)
Pennisetum purpureum Schumach. is a weed that is currently spreading rapidly to many parts of the world particularly tropical countries. The abundance of P. purpureum in Malaysia is presently a serious problem. A study was conducted to investigate and evaluate the potential allelopathic effects of P. purpureum on Eleusine indica L. Gaertn. using the aqueous leaf extract and plant debris incorporated into the soil. Low concentrations of the P. purpureum aqueous extract (2%) and debris incorporated into the soil (25/500 g) inhibited germination and seedling growth of the bioassay species (E. indica) by >80%. The responses of the bioassay species to the aqueous extract and debris-incorporated soil were concentration dependent. The aqueous extract had higher total phenolic content compared to that from the debris incorporated soil, indicating the presence of certain phytotoxic compounds in the leaf debris and leaf extracts.